FIXED COMBINATION OF VALSARTAN AND AMLODIPINE: EFFECTS ON THE LEFT VENTRICULAR HYPERTROPHY REGRESSION, ALBUMINURIA REDUCTION AND ENDOTHELIUM FUNCTION IN HYPERTENSIVE PATIENTS WITH METABOLIC SYNDROME - Ye. I. Tarlovskaya; N. S. Maksimchuk; I. Ye. Sapozhnikova; S. V. Malchikova (Рациональная фармакотерапия в кардиологии)
Aim. To study effects of fixed combination of valsartan and amlodipine on of left ventricular hypertrophy (LVH) regression, microalbuminuria reduction and endothelium function in hypertensive patients with metabolic syndrome (MS).Materials and methods. 20 hypertensive patients (15 females and 5 males) with metabolic syndrome and a history of previous ineffective antihypertensive therapy were studied. Combined antihypertensive therapy was applied during 12-24 weeks. Amlodipine and valsartan dose was 5/160 or 10/160 mg/day depending on blood pressure level. Endothelial function, blood pressure level, urinary albumin excretion and LVH regression were estimated.Results. Blood pressure reduction to the target level was revealed. There was a significant reduction in microalbuminuria by -55.3±39.2% (р=0.022) in comparison with the baseline. Endothelium-dependent vasodilation increased in 3.6±7.2% (р=0.05) in comparison with baseline, LVH decreased by -9.1±12.4 g/m2 (р=0.021).Conclusion. Therapy with fixed combination of valsartan and amlodipine results in blood pressure and microalbuminuria reduction, endothelium-dependent vasodilation improvement, LVH regression in hypertensive patients with MS. These findings show that the fixed combination of these antihypertensives has a multifaceted impact on cardiovascular risk.